(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Shakawi AMHA, Hassan R, Mustapah DS. 2022. Effects of water parameters on population structure of mud crab from Buntal Mangroves, Kuching, Sarawak, Malaysia: A GLM analysis. Biodiversitas 23: 2580-2585. Buntal Mangroves, Kuching, Sarawak, Malaysia, is an area that is abundant with biological resources but contains minimal biodiversity information. Mud crab fisheries by the locals exist on small scales at Buntal Mangroves, but there is a tendency to overfish due to the increasing demand for this resource. The relationship between the population structure of mud crabs and the environmental factors in Buntal Mangroves has not been explored. Therefore, this study aimed to apply the generalized linear models (GLM) for analyzing the population structure of mud crabs with selected water parameters in Buntal Mangroves. Scylla olivacea (Herbst, 1796) has the highest abundance in Buntal compared to S. tranquebarica (Fabricius, 1798) and other types of mud crab. Three GLM with carapace length, carapace width, and body weight as dependent variables were constructed. These GLMs with gamma-distributed response variables indicated that depth, pH, salinity, and turbidity positively affected body weight, carapace width, and carapace length, while temperature had a negative impact on the dependent variables. The results emphasized the importance of adopting the GLM to describe a relationship where the response variable followed a non-normal distribution. The findings provide a basis for future studies at Buntal Mangroves, not only for conservation purposes but also to support the utilization of this valuable resource sustainably.